O processo de poluição ambiental e alimentar por agrotóxicos em municípios da bacia do Rio Juruena, Mato Grosso - Oliveira, Luã Kramer de (2016)
This work consists of an analysis of the contamination process by pesticides in the environment (surface water and sediment) and in food (fish, beef and sheep meat) in municipalities of large agricultural production in Mato Grosso state, located in the river basin Juruena. The general objective of this study was to analyze the use of pesticides in agricultural production and the environmental and food contamination by pesticides in the municipalities of Campo Novo do Parecis, Sapezal and Campos de Júlio. As a theoreticalmethodological reference, we used the Critical Epidemiology and the Pesticides Surveillance proposal. The research had the participation of the community and sectors of the State. In each municipality, one school in the urban area and one in the rural area, participated as a scientific basis for research. We used the database of the land structure and agricultural production, made available by the Brazilian Institute of Geography and Statistics. Water, sediment and fish samples from rivers and streams, and bovine and ovine meat were collected in the municipalities, for the laboratory analysis of residue tests for pesticides. We have identified a concentrator land ownership and wealth, built in an oligarchic and authoritarian historical process in Mato Grosso, forming the basis of the economy and politics in these municipalities. The agricultural production of soybeans, corn, cotton, sunflower, sugar cane and beans, and extensive cattle raising are of immense proportions and condition socioecological-spatial dynamics in these territories. The standard annual usage of millions of liters of pesticides in these large farms was characterized as 'rural chemical pollution' and as 'imposed exposition' by pesticides to the population and the environment. Among the particular processes of rural chemical pollution by pesticides in the municipalities, the most significant identified are the transgenic seeds and the use of glyphosate, the emergence of the Helicoverpa armigera caterpillar with the release of benzoate emamectin, the release of the soybean and the resistant transgenic maize to 2,4-D and the high use of insecticides in cotton crops. Of the 18 water samples collected, in 07 samples, residues of the active ingredient atrazine (0.03-0.20 ppb) were detected. Of the 17 sediment samples collected, there was no detection of pesticide residues. Of the 18 fish samples analyzed by the multiresidue technics, 02 active ingredients were detected: a sample composed of Carás with flutriafol (3-10 ppb) and a sample of Trairão with atrazine (1,5-5 ppb). In the 41 samples of cattle and sheep meat collected there was no detection of residues of pesticides. We understand that the detection of atrazine in water and fish meat and flutriafol in fish meat are critical to health and the environment and indicate the contamination of other pesticides at collection points. We systematized the hypothesis of 'ceva' and ration for fish, as a possible route of rural chemical pollution by pesticides in the water system and in the fish organism. We identify barriers to the study of rural chemical pollution by pesticides in cattle and sheep, and describe the critical process of 'dangerous interaction between livestock and crops agrochemical'.